Responsiveness of Restaurateurs toward Implementation of Environmentally Friendly Practices: The Case of Independently Owned Casual Upscale Restaurants in Penang - Anida, Ismail (2009)
The study of environmental management in the restaurant industry has been few and far between. One of the reasons could be due to the solitary nature of the restaurant, which unless under a chain or franchise, is usually privately owned. Being an independent small enterprise, a restaurant's impact on degradation of the environment could perhaps be underestimated. This study contradicts this postulation by looking at the various literatures that discuss restaurants' effect on the environment and the measures available to help the industry be more environmentally friendly. The purpose of this study is to examine internal and external drivers and barriers that may contribute to the responsiveness of restaurateurs toward implementation of environmentally friendly practices (IEFPs). Several internal organizational factors are found to influence the propensity of IEFPs in the restaurant business: top management, cost considerations to implement environmentally friendly practices (EFPs) and employee connectedness. The external organizational factors are: environmental law and regulations, green supply chain, competitive advantage (trade pressure), stakeholders' (i.e. customers and community) demands. This study reports the findings from a survey administered among 26 restaurateurs of the casual upscale type in Penang, supplemented with interviews conducted with five of the restaurateurs, government officials, a NGO representative and recycle business operators. The findings show IEFPs deficiently exists in the restaurant sector. Restaurateurs are rather receptive toward the concept of IEFPs but are reluctant to invest in an Environmental Management System (EMS). In addition, the espousal of IEFPs is impeded by archaic environmental laws and regulations coupled with little enforcement by authorities; scarce and intermittent green supply chain; nonexistent trade pressure; and poor environmental awareness among customers and community, hence diminishing demand for restaurateurs to implement EFPs. An understanding of the mechanisms and key drivers and barriers to implement EFPs can facilitate the conception of a feasible framework fitting for independently owned upscale restaurant in Penang specifically, and can potentially be expanded to suit other segments in the restaurant industry. In this instance, the study also depicts the responsiveness of restaurateurs towards IEFPs in the context of a developing country.